KOLABORASI ANTAR INDUSTRI DALAM EKONOMI SIRKULAR: KAJIAN LITERATUR PADA MODEL SINERGI - Loso Judijanto; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
The circular economy is an increasingly important concept in efforts to achieve sustainable development in the modern era. One key aspect of realising a circular economy is collaboration between industries, which is often realised through synergy models. These models enable various industries to exchange resources, energy, and information, creating a more efficient and environmentally friendly system. A review of various literature shows that the application of synergy models in the context of a circular economy can provide various benefits. These include waste reduction, increased resource efficiency, lower production costs, and improved industrial competitiveness. However, the implementation of this model also faces challenges, such as the need for complex coordination among stakeholders and significant initial investment. Despite these challenges, the potential offered by synergy models in promoting a circular economy is enormous. The success of implementing this model depends on close collaboration among various parties, appropriate policy support, and sustainable technological innovation. Thus, further development and adoption of synergy models could be key to achieving a more sustainable and efficient economic system in the future.